Estrategias metodológicas para desarrollar el pensamiento crítico, en el bloque curricular 6 del área de Lengua y Literatura, en los niños de décimo grado, pertenecientes a la escuela de educación general básica Miguel Riofrío Nº 1 de la ciudad de Loja. Período 2013-2014 - Elizalde Rivera, Julia Patricia (2015)
This research entitled: METHODOLOGICAL STRATEGIES TO DEVELOP CRITICAL THINKING IN BLOCK 6 OF AREA CURRICULUM LANGUAGE ARTS IN CHILDREN OF TENTH GRADE, BELONGING TO THE BASIC GENERAL EDUCATION SCHOOL MIGUEL RIOFRÍO # 1 of the city of Loja. PERIOD 2013-2014, whose overall objective is: Determine the methodological strategies to develop critical thinking among students in tenth grade, School of Basic General Education Miguel Riofrío No. 1. Descriptive, transverse and quasi- experimental design was used to conduct this research, plus the following methods were used: scientific, comprehensive, analytical, synthetic, participatory diagnosis, proactive model, workshop and tool: evaluation, also used as a technique direct observation Tab and surveys: questionnaire, which were applied to the population took 24 students and 1docente. At the conclusion of this research work can manifest that most students do not have adequate development of critical thinking and this is because the teacher only uses basic strategies for that reason it is concluded that the application of the model of teaching resources by research by the method of workshop, directly benefited the students and teachers, helping to reduce the difficulties in the development of critical thinking demonstrated through the Pearson r